Impact of Cyproterone Acetate and Ethinylestradiol on Clomiphene Resistant PCOS Patient with High Serum AMH level (Journal of Shaheed Suhrawardy Medical College, 2021)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women of reproductive age. PCOS is characterized by hyperandrogenism and oligomenorrhea, and Polycystic ovary .It is a common cause of female subfertility. Anti-mullerianhormone (AMH) is 2-4 times higher in patients with PCOS compared to normal subfertilety patient.Objective: To assess the impact of metformin and oral contraceptives (OCs) containing cyproterone acetate and ethinyl estradiol on serum anti-Mullerian hormone (AMH) levels, with CC resistant polycystic ovary syndrome (PCOS)Methods: This prospective randomized controlled trial was conducted at Bangabandhu Sheikh Mujib Medical University(BSMMU), Dhaka during the preoid of January 2019 to june 2019. Already diagnosed patients of polycystic ovary syndrome with subfertility with high serum AMH level more than 5 ng/ml attending in the OPD of Reproductive Endocrinology and infertility department at BSMMU are the study population. Total 60 subjects fulfilling rotardum criteria and who are treated with 3 cycle CC with 100mg /day for 5 days from day 2 of menstrual cycle but fail to ovulate were recruited for the current study. Those subjects with tubal, and male factors excluded from the study. .After enrollment of the patients, randomization will be carried out by blocked randomization method to divide them equally into two groups-Group A number of patients 30 ( treated with2mg cyproterone acetate (CPA) and 35 mcg of ethinylestradiol (EE) and Group B number of patients 30 treated with Metformin). Group A patients will receive treatment with 2mg cyproterone acetate (CPA) and 35 mcg of ethinylestradiol (EE) for 6 months and Group B patients will receive treatment with Metformin for 6 months . After enrollment of the patients, base line hormonal assessment basal level of FSH, LH ,thyroid-stimulating hormone (TSH), prolactin (PRL), and testosterone hormones were registered and metabolic assessment included OGTT and fasting insulin level were done, and to identify the changes in clinical and biochemical profile of study population. Clinical evaluation, by history and examination, transvaginal ultrasonography of both group and changes of the above mentioned parameters of both group were recorded after 6 month of completion of treatment.Results: A Changes in clinical parameters (Acne, BMI, Menestrual cycle) was recorded every three monthly for 6 month. Changes of biochemical parameters (serum LH (D2), serum FSH (D2), serum testosterone, OGTT and fasting insulin), serum AMH were recorded every three monthly for 6 month. Changes of sonographic parameters (ovarian volume, Antral follicular count development, was done monthly for 6 cycles. AMH levels are significantly reduced under treatment with OCP containing 35mg ethinylestradiol plus 2 mg cyproteroneacetate than metformin. AMH was significantly decreased after treatment with 35 mg ethinylestradiol plus 2 mg cyproterone acetate ( p < 0.001 at 6 months). and treatment with metformin did not significantly affect serum AMH levels. AMH was significantly decreased after treatment with metformin (p < 0.005). Serum LH was and OGTT was significantly decreased in both treatment p